An Integrated Model of WebQual 4.0 and SERVQUAL: Answer to the Next Research Call - Siti Mardiana (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2023)
In the original paper of WebQual 4.0, Barnes and Vidgen (2002) called for an improvement of their WebQual 4.0 model. Since WebQual 4.0 is a tool for assessing the quality of e-commerce websites, therefore a modification should be made in order to use WebQual 4.0 for other types of websites. This research offers an integrated model of WebQual 4.0 and SERVQUAL to fulfill the need. The proposed integrated model resulted in seven variables: Usability, Design, Information, Empathy, Responsiveness, Assurance, and Reliability. To test the model, a questionnaire based on the proposed model was created to assess the quality of a company website that is primarily used to manage employeesâ€™ data. Â There were 124 data samples that can be used for analysis. A spider web diagram was created based on the reliability (Cronbachâ€™s alpha) scores to show the overall website quality. Based on the confirmatory factor analysis (CFA) results, it can be concluded that the integrated model that was created in this research was considered a good model. The implications and lessons learned from the study were discussed in the paper.